ANALYSIS OF FACTORS AFFECTING ORGANIZATIONAL WORK CULTURE IN COMPANIES - Theresia Mastiur Ningsih Siagian (The American Journal of Interdisciplinary Innovations and Research, 2024)
Every company in Indonesia has a different work culture, one of which is Garuda Indonesia, where the corporate culture at Garuda tends to be rigid and work relationships are influenced by personal closeness, thus affecting the placement of people in the organizational structure, where in the organizational structure there are people with different characters and will bring different work cultures. In addition, the work culture at Garuda is also influenced by management styles with different characters, where the management style in directing the organization in the company is different, thus affecting the vision and mission carried out by the company in the future, where the management style at Garuda adopting a transformational management style, but in reality the transformational style is not carried out and tends to be a leadership style that is undemocratic and tends to be authoritarian, so that there is discomfort from employees and makes employees feel heavy pressure, so that their competencies do not come out as they should for the sustainability of employees, so that affect Garuda's performance which continues to decline. The research method used is descriptive quantitative by using analysis multiple linear regression using SPSS 22. The population of this study is the management in several companies in Indonesia totaling 100 people / person, where the sampling technique in this study uses the census method, with a sample of 100 people the existing management in several companies in Indonesia through the distribution of questionnaires conducted using online. The results of the study which are based on the hypothesis partially state that the management style variable affects the work culture of companies in Indonesia, and simultaneously the organizational structure, organizational characteristics and management style variables affect the work culture of companies in Indonesia.